2005
DOI: 10.1126/science.1116251
|View full text |Cite|
|
Sign up to set email alerts
|

Direct Evidence for a Parietal-Frontal Pathway Subserving Spatial Awareness in Humans

Abstract: Intraoperative electrical stimulation, which temporarily inactivates restricted regions during brain surgery, can map cognitive functions in humans with spatiotemporal resolution unmatched by other methods. Using this technique, we found that stimulation of the right inferior parietal lobule or the caudal superior temporal gyrus, but not of its rostral portion, determined rightward deviations on line bisection. However, the strongest shifts occurred with subcortical stimulation. Fiber tracking identified the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
332
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 595 publications
(380 citation statements)
references
References 25 publications
37
332
1
1
Order By: Relevance
“…These results confirm models according to which disrupted integrity of right-hemisphere frontoparietal networks is a core pathophysiological mechanism in neglect syndrome (Corbetta and Shulman, 2011;Bartolomeo et al, 2012). So far, a disconnection of right fronto-parietal networks in neglect has been demonstrated at the neuroanatomical and neurofunctional level using in-vivo tractography (Thiebaut de Schotten et al, 2005, 2011, lesion mapping (Ptak and Schnider, 2010;Lunven et al, 2015), fMRI (He et al, 2007;Bartolomeo et al, 2012) and resting state networks analysis of MRI and EEG (Baldassarre et al, 2014;Fellrath et al, 2016). However, the role of transient functional synchronization as a network-based mechanism underlying perceptual deficits in neglect has not been identified.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results confirm models according to which disrupted integrity of right-hemisphere frontoparietal networks is a core pathophysiological mechanism in neglect syndrome (Corbetta and Shulman, 2011;Bartolomeo et al, 2012). So far, a disconnection of right fronto-parietal networks in neglect has been demonstrated at the neuroanatomical and neurofunctional level using in-vivo tractography (Thiebaut de Schotten et al, 2005, 2011, lesion mapping (Ptak and Schnider, 2010;Lunven et al, 2015), fMRI (He et al, 2007;Bartolomeo et al, 2012) and resting state networks analysis of MRI and EEG (Baldassarre et al, 2014;Fellrath et al, 2016). However, the role of transient functional synchronization as a network-based mechanism underlying perceptual deficits in neglect has not been identified.…”
Section: Discussionsupporting
confidence: 85%
“…Second, converging evidence exists for the role of the integrity of fronto-parietal networks in neglect pathology. It has been shown that the functional inhibition of fronto-parietal connections generates an intraoperative neglect-like pattern during a bisection line task in patients undergoing surgery (Thiebaut de Schotten et al, 2005). Using lesion-symptom mapping and fractional anisotropy, specific components of fronto-parietal fibers have been isolated that are responsible for the deficits in modulation of attention by task relevance (Ptak and Schnider, 2010) and for severity of chronic symptoms in neglect (Lunven et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the HAROLD model, our data are indicative of asymmetries in hemispheric processing in the direction of the attentional orienting hypothesis (Heilman & Van Den Abell, 1979;Reuter Lorenz et al, 1990) and suggest that tasks like visuo-spatial line bisection, tactile rod bisection and mental number line bisection predominantly engage attentional orienting mechanisms in the right parietal cortex (Thiebaut de Schotten et al, 2005;Varnava et al, 2013). We assert, based on the present data, that a very similar neural signature is produced in older adults.…”
contrasting
confidence: 77%
“…This 'Attentional Orienting Hypothesis' is very well supported by behavioural data (Bultitude & Toba, Cavanagh & Bartolomeo, 2011), neuroimaging data (Thiebaut de Schotten, Urbanski, Duffau et al, 2005;Thiebaut de Schotten, Dell'Acqua, Frokel et al, 2011;Varnava, Dervinis & Chambers, 2013) and clinical data -patients with right hemisphere damage err rightward not leftward on spatial tasks (Dormal, Schuller, Nihoul & Pesenti & Andres, 2014;Manfredini, Mancini, Posteraro & Savazzi, 2013;Robertson & Marshall, 1993).…”
Section: Introductionmentioning
confidence: 71%
“…First, lesions to the ventral attention network are linked to disrupted activity and functional connectivity in the PPC (a key region of the dorsal attention network), and the magnitude of these disruptions predicts the degree to which neglect patients are impaired at reorienting spatial attention to targets in the contralesional visual field (He et al, 2007). Second, damage to the superior longitudinal fasciculus, which connects inferior parietal regions in the TPJ to dorsal frontal regions that contribute to orienting spatial attention (e.g., the FEF and the DLPFC), is associated with the rightward spatial bias that typically characterizes neglect (Shinoura et al, 2009;Thiebaut de Schotten et al, 2005). Third, the dorsal and ventral attention networks are coactivated in functional neuroimaging studies of healthy controls during unanticipated shifts of covert visual spatial attention Kincade et al, 2005).…”
mentioning
confidence: 99%